Evidence to Support a Conspecific Nature of Allopatric Cytological Races of Anopheles nitidus (Diptera: Culicidae) in Thailand - Songsawatkiat, Siripan (Oxford University Press, 2014)

(untitled) (J Insect Sci)
Metaphase karyotype investigation on two allopatric strains of Anopheles nitidus Harrison, Scanlon, and Reid (Diptera: Culicidae) was conducted in Thailand during 2011–2012. Five karyotypic forms, i.e., Form A (X (1) , Y (1) ), Form B (X (1) , Y (2) ), Form C (X (2) , Y (3) ), Form D (X (1) , X (3) , Y (4) ), and Form E (X (1) , X (2) , X (3) , Y (5) ) were obtained from a total of 21 isofemale lines. Forms A, B, and C were confined to Phang Nga Province, southern Thailand, whereas Forms D and E were restricted to Ubon Ratchathani Province, northeastern Thailand. Cross-mating experiments among the five isofemale lines, which were representative of five karyotypic forms of An. nitidus , revealed genetic compatibility by providing viable progenies and synaptic salivary gland polytene chromosomes through F (2) generations. The results suggest that the forms are conspecific, and An . nitidus comprises five cytological races. The very low intraspecific sequence variations (average genetic distances = 0.002–0.008) of the nucleotide sequences in ribosomal DNA (internal transcribed spacer 2) and mitochondrial DNA (cytochrome c oxidase subunits I and II) among the five karyotypic forms were very good supportive evidence.